The role of Fusarium and Alternaria in the bio-degradation of round up pesticide - Kadhim, Majid (Al-Qadisiyah Journal of Pure Science, 2017)
The present study aimed to investigating the role of soil fungi in the biodegradation of the round up pesticide . The study focused on two of the fungi , Alternaria and Fusarium which were isolated from soil . The used concentrations of round up were (0, 30,40,50,60,) part per million added to samples of soil tainted with the fungal inoculums . The samples were then incubated at 27 cÂº for (0,3,6,9) days at the end of which the pesticide was extracted and the residues of it was estimated through the Gas chromatography method . The study also investigated the influence of some other factors on the two fungi mentioned above and its role in the biological degradation of round up . The factors included temperature , pH , amount of fungal inoculums used and the effect of pesticide on the fungi at solid media. Results showed that the two fungi have significant ability in degradation of the pesticide especially when using 40 ppm in of the Fusarium and 30 ppm for Alternaria .The two concentrations resulted in the percentages of degradation (%19.25 and %13.33 ) respectively . The optimal temperature for degradation was 25cÂ° and pH was 7 while the amount of fungal inoculums correlated positively with the two fungi s ability in enhancing pesticide degradation .It was also found that the two fungi are able to withstand the low concentrations of pesticide using it as food source while high concentrations lead to the prohibition of the growth of the two fungi .